2023
DOI: 10.3390/vaccines12010002
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Mortality Predictors in Hemodialysis Patients Infected with COVID-19: Impact of Vaccination Status

Voin Brkovic,
Gorana Nikolic,
Marko Baralic
et al.

Abstract: The global outbreak of COVID-19, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has prompted significant public health concerns. This study focuses on 442 chronic hemodialysis patients diagnosed with COVID-19, emphasizing the impact of vaccination status on clinical outcomes. The study investigates the correlation between vaccination status and laboratory findings, aiming to identify predictive factors for mortality. Results indicate that vaccination status plays a crucial role in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Due to the lack of data on the adverse effects of the SARS-CoV-2 vaccine in the PD patient population, a safety profile study would be of great importance. A study on the population of HD patients showed that the m RNA vaccine leads to the creation of a higher titer of Ab, but also to a faster weakening of the immune response, and research by Brković et al showed a significant impact of vaccination on the survival of the HD population compared to unvaccinated patients [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack of data on the adverse effects of the SARS-CoV-2 vaccine in the PD patient population, a safety profile study would be of great importance. A study on the population of HD patients showed that the m RNA vaccine leads to the creation of a higher titer of Ab, but also to a faster weakening of the immune response, and research by Brković et al showed a significant impact of vaccination on the survival of the HD population compared to unvaccinated patients [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%